Pengaruh DER, ROA, TATO Terhadap Harga Saham Bank Umum Yang Terdaftar Di BEI - Sanusi, Ruchan; Balafif, Muhammad; Shanti, Laily Kartika Arya (Asosiasi Dosen Akuntansi Indonesia, 2024)
This research aims to determine the influence of debt-equity ratio, Return on Assets, and Total Asset Turnover on stock prices simultaneously, partially, and dominantly in Commercial Banks listed on the Indonesian Stock Exchange for the 2020-2022. The type of research is quantitative. The sampling technique was carried out using purposive sampling. The samples taken were 45 banks. The data collection technique is looking at the annual financial report via the official IDX website. The data analysis technique is multiple linear regression analysis and simultaneous, partial, and dominant tests. This research shows that Debt to Equity Ratio, Return on Assets, and Total Asset Turnover significantly affect stock prices. Partially, the Debt-to-equity ratio has a negative and insignificant effect on stock prices, return on assets has a positive and significant effect, and total asset turnover has a positive and significant effect on stock prices. Dominantly is Return on Assets. This result is strengthened by the coefficient of determination value of 58.4%.